The Senate of Constantinople in the eleventh century: the crystallization of a space of real power (Iter, 2022)
In the next assignment we will realized some approaches about the rol politicianthat the Constantinople's senate occupied inside of the institutional scaffolding of the Eastern roman empire. About o f little reconstruction o f the origin of the institutesenatorial, where we will analyzed the social composition o f the members of thesame, we will focus our attention in the XI century. Traditionally considered thiscentury like a “not turning point” for the structural framework of the Easternempire, view the simultaneous crisis o f a political, military and economic naturethat transited their respective subsystems, we will pretend highlight how theSenate was becoming in a space o f power that really could come to exercise a truly“institutional pressure”. However, our analysis c o u ld n 't escape in comparativeperspective another institutes that they exercised like “interested groups”:theimperial Army and the Patriarchy of Constantinople.
Keywords: Senate - Eastern roman empire - interest groups